2010
DOI: 10.1111/j.1750-3841.2010.01875.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherent Properties and Macrophage Activation Ability of 3 Strains of Lactic Acid Bacteria

Abstract: Lactic acid bacteria (LAB) must possess probiotic properties in order to be beneficial to humans and animals. The adherent properties, the acid and bile tolerance as well as the macrophage activation ability of isolated LAB strains were investigated in this study. The adhesion was analyzed following heat, acid, trypsin, and sodium periodate treatments. Production of the cytokine tumor necrosis factor-α (TNF-α) by RAW 264.7 macrophages was also measured after stimulation with heat-killed LAB strains. The viable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…In order to exert health-enhancing benefits, probiotics must possess certain potentials such as the ability to withstand passage through the GIT, adherence to mucus and/or human epithelial cells and cell lines, reduction of pathogen adhesion to surfaces through aggregation and inhibition of enteric pathogens [4,5]. The acidity of the human GIT depending on the food substrate and the intervals of feeding vary from pH 1.5 to 4.5 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to exert health-enhancing benefits, probiotics must possess certain potentials such as the ability to withstand passage through the GIT, adherence to mucus and/or human epithelial cells and cell lines, reduction of pathogen adhesion to surfaces through aggregation and inhibition of enteric pathogens [4,5]. The acidity of the human GIT depending on the food substrate and the intervals of feeding vary from pH 1.5 to 4.5 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Their benefits include alleviation of lactose intolerance, enhancing nutrients bioavailability, and prevention or reduction of the prevalence of allergies in individuals with high susceptibility [7]. Probiotics need to have certain potential, such as the ability to tolerate GIT passage, adherence to mucus and human epithelial cells, competing for space against pathogenic microbes through aggregation and inhibition of enteric pathogens [8]. LAB and bifidobacterium are commonly used in commercially available probiotic products.…”
Section: Anti-microbial Activity Of Potential Probiotic Lactic Acid Bmentioning
confidence: 99%
“…Bile salt hydrolase activity was conducted as described by [22]. Bile salt hydrolase (BSH) activity was screened by growing 10 μ l of the prepared overnight culture on MRS agar plate supplemented with 0.37 g/l CaCl 2 with 5g/l so-Anti-microbial activity of potential probiotic lactic acid bacteria against Methicillin-Resistant Staphylococcus Aureus (MRSA) 8 dium salt of taurodeoxycholic acid. Plates incubated at 37°C for 3 days.…”
Section: Bile Salt Hydrolase Activitymentioning
confidence: 99%
“…it represents an attractive force between cells and/or inert surfaces principally due to the role of electron-donor/electron-acceptor interactions between the two surfaces (Bellon-Fontaine, Rault, & van Oss, 1996). Bacterial cell surface hydrophobicity has often been assessed by adhesion to solvents or hydrocarbons (Del Re, Sgorbati, Miglioli, & Palenzona, 2000;Kos et al, 2003;Mathara et al, 2008;Schillinger, Guigas, & Heinrich Holzapfel, 2005;Vinderola & Reinheimer, 2003), based on the comparison between bacterial cell affinity to a monopolar and a polar solvent. The monopolar solvent could be acidic (electron acceptor) or basic (electron donor) but must have similar van der Waals properties (Bellon-Fontaine et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The monopolar solvent could be acidic (electron acceptor) or basic (electron donor) but must have similar van der Waals properties (Bellon-Fontaine et al, 1996). High cell surface hydrophobicity has been correlated to increased cell-to-cell adhesion (Del Re et al, 2000;Kos et al, 2003;Schillinger et al, 2005) and suggested to play significant role in interaction with organic mucin layer of the gut (Mathara et al, 2008) and adhesion to epithelial cells (Schillinger et al, 2005). acid and pepsin of gastric juice and guards the host against infections by pathogens ( Zhou, Gopal, & Gill, 2001;Juge, 2012;Uchida et al, 2006).…”
Section: Introductionmentioning
confidence: 99%